Sistem Informasi Penjadwalan Produksi Pada Cv. Bulu Nusantara Gresik - Sugianto; Emmy Wahyuningtyas (Informatics Engineering Department-UWKS, 2019)
To obtain optimum results, then all production activities must first be planned well. Production Scheduling is used to get an effective job assignment, in order to avoid job buildup so as to reduce idle time. Therefore it needs to be scheduled regularly so that the production work can be completed properly and delivery time is not delayed. In this paper the authors want to create an information system that can plan scheduling automatically generate the production schedule. In this system is applied forward scheduling method of scheduling production activities of a process will produce a production work report